Control of postharvest gray mold of ‘BRS Nubia’ table grape under cold storage - Ronan Carlos Colombo; Deived Uilian de Carvalho; Maria Aparecida da Cruz; Ciro Hideki Sumida; Saeed Ahmed; Muhammad Shahab; Sergio Ruffo Roberto (Semina: Ciências Agrárias, 2020)
The demand for high-quality nutritional products has increased fruit consumption, as grapes, for this reason postharvest techniques are required to prevent losses, to preserve quality, to extend shelf life, and to attend to consumer needs. In this way, the objective of this study was to evaluate strategies to control gray mold caused by Botrytis cinerea in ‘BRS Nubia’ grapes during cold storage and shelf life periods. Grape bunches were harvested from a commercial vineyard in Marialva, Parana, Brazil. Grapes were subjected to the following treatments: cold storage at 2 ºC (control), cold storage at 2 ºC with SO2-generating pads, cold storage at 2 ºC and inoculated with B. cinerea suspension, and cold storage at 2 ºC with SO2-generating pads and inoculated with B. cinerea suspension. The experiment was conducted in a complete randomized design with five replications per treatment using four bunches per experimental unit. A factorial arrangement (absence/presence of SO2 pads × absence/presence of Botrytis inoculation) was applied. At the end of 30 days of cold storage and 7 days of shelf life (22 ºC), gray mold incidence, shattered berries, and physicochemical parameters were evaluated. The gray mold incidence on ‘BRS Nubia’ grapes decreased when SO2-generating pads were used during cold storage. Berry weight loss was greater in the treatments without SO2-generating pads after 30 days of cold storage followed by 7 days of shelf life. Berry firmness, soluble solids content (SS), total acidity (TA), SS/TA ratio, and anthocyanins concentration were not negatively affected by SO2-generating pad treatments. However, a slight increase in the shattered berries percentage was recorded for the SO2-generating pad treatments. No significant quality loss of ‘BRS Nubia’ grape was evident after 30 days of cold storage followed by 7 days of exposure at room temperature. In this context, SO2-generating pads can be used to control the gray mold incidence on ‘BRS Nubia’ table grapes during cold storage.